Understanding competency of nursing students in the course of case-based learning in Cambodia: a convergent mixed method study - Kyoko Koto-Shimada; Rogie Royce Carandang; Akira Shibanuma; Junko Kiriya; Ken Ing Cherng Ong; Sokneang Touch; Virya Koy; Masamine Jimba (BMC, 2023)
Abstract Background In the last decade, nursing education has begun to reform to competency-based education worldwide, including in low-and middle-income countries. Case-Based Learning (CBL), an approach to delivering competency-based education, contributes to acquiring critical thinking competency, problem-solving, higher knowledge, professional value and attitude. However, it needs to be taught in a culturally appropriate manner. In Cambodia, CBL was initiated in a classroom and clinical practicum by faculty and preceptors who graduated from the upgrading course. This study examined the factors associated with the competency level of nursing students, explored the practice and perceptions of teaching-learning activities among students, faculty members and preceptors and assessed the coherence of qualitative and quantitative findings. Methods This was a convergent, mixed methods study. Data were collected from eight educational institutions for quantitative and qualitative studies and seven hospitals for qualitative studies. From June to September 2019, a cross-sectional survey of nursing students in the third year of the three-year programme (n = 719), eight focus group discussions (FGDs; n = 55) with 6-8 members and 15 FGDs with faculty (n = 38) and clinical preceptors (n = 37) with 4-7 members were conducted to elicit the teaching-learning experience and perceptions. Multiple linear regression was performed to investigate the factors associated with student competency. Moreover, the study conducted thematic content analysis on the qualitative data. The integrated analysis was presented as side-by-side joint displays. Results First, the quantitative and qualitative findings confirmed each other 's CBL learning experiences. Students had higher levels of nursing competencies if they had CBL experiences, both in the classroom and clinical practicum, both in a group manner. Next, the quantitative and qualitative findings complemented students' academic satisfaction with the teaching by faculty members and preceptors. Finally, the quantitative and qualitative findings were expanded to explain students' academic satisfaction with the programme. Conclusions The finding of CBL experiences in a group and students' satisfaction with faculty members' and preceptors' teaching improved nursing students' competency development. Meanwhile, students' satisfaction with the design and delivery of the educational programme provides implications for policy level to narrow the theory and practice gaps in low- and middle-income countries.